Nano Differential Scanning Fluorimetry-Based Thermal Stability Screening and Optimal Buffer Selection for Immunoglobulin G - Soo Hyun Kim; Han Ju Yoo; Eun Ji Park; Dong Hee Na (MDPI AG, 2021)
Nano differential scanning fluorimetry (nanoDSF) is a high-throughput protein stability screening technique that simultaneously monitors protein unfolding and aggregation properties. The thermal stability of immunoglobulin G (IgG) was investigated in three different buffers (sodium acetate, sodium citrate, and sodium phosphate) ranging from pH 4 to 8. In all three buffers, the midpoint temperature of thermal unfolding (Tm) showed a tendency to increase as the pH increased, but the aggregation propensity was different depending on the buffer species. The best stability against aggregation was obtained in the sodium acetate buffers below pH 4.6. On the other hand, IgG in the sodium citrate buffer had higher aggregation and viscosity than in the sodium acetate buffer at the same pH. Difference of aggregation between acetate and citrate buffers at the same pH could be explained by a protein-protein interaction study, performed with dynamic light scattering, which suggested that intermolecular interaction is attractive in citrate buffer but repulsive in acetate buffer. In conclusion, this study indicates that the sodium acetate buffer at pH 4.6 is suitable for IgG formulation, and the nanoDSF method is a powerful tool for thermal stability screening and optimal buffer selection in antibody formulations.